Management of the object-oriented development process - Liu, Liping; Roussev, Boris (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This book offers technical skills as well as strategic insights on how to manage software projects, deploy object-oriented software development processes, understand the current trends and make the transition from structured to object-oriented techniques